(untitled) (Current Horticulture, 2024)
The study was carried out at ICAR-Indian Agricultural Research Institute, New Delhi, to study the response of packaging materials, viz. woven bag, high density polyethylene (HDPE) 51 micron , low-density polyethylene (LDPF) 25 micron, muslin cloth bag and bamboo basket (control, without packaging) and two storage conditions, i.e. ambient condition (22) and cold storage (or low temperature) condition (and 85-95% relative humidity) on keeping quality attributes of loose flowers of single petalled tuberose (Polianthes tuberosa Linn.) cv. Arka Prajwal. Fully developed unopened florets were harvested in early morning (before sunrise). The packaging and storage condition significantly influenced all parameters. Among all treatments, loose flowers packed in HDPE 51 micron bag and stored under cold storage recorded maximum flower diameter (8.99 mm), flower opening index (77.85%), colour (whiteness) index (89.13%) and shelf-life (6.00 day) of loose flowers under cold storage condition. On the other hand, in control treatment the above said parameters recorded were 6.98 mm, 50.00%, 54.10% and 3.50 day, respectively. Under ambient condition, maximum flower diameter (8.08 mm), flower opening index (66.00%), colour index (91.85%) and shelf-life (4.00 day) of flowers were recorded with HDPE 51 micron packaging. In control treatment, these parameters were 6.73 mm, 50.00%, 63.77% and 1.50 days, respectively. Thus, it can be concluded that among packaging materials HDPE 51-micron thickness bag was found to be the best for packing of loose flowers of tuberose cv. Arka Prajwal under both ambient and cold storage conditions.